Porgy and Miles - Tucker, Mark (Current Musicology, 2001)
Miles Davis traced his rising fame in the 1950s to changes taking place in society. “There was a new mood coming into the country,” he stated in his autobiography. “Black and white people were starting to get together, and in the music world Uncle Tom images were on their way out.” Describing himself as a “nonconformist”-“cool and hip and angry and sophisticated and ultra clean”-Davis identified with others in that period who were breaking barriers and challenging authority: Martin Luther King leading the Montgomery bus boycott, Marian Anderson appearing as the first black singer at the Metropolitan Opera, Marlon Brando and James Dean gaining popularity as actors by portraying rebels (Davis 1989:197-98). Davis’s bold, brash persona earned him a special degree of respect from black Americans. Writer Amiri Baraka considered the trumpeter his “ultimate culture hero,” someone who embodied “a black attitude that had grown steadily more ubiquitous in the 1950s-defiance” (Baraka 1996:41, 48). Given Davis’s affiliation, first with a group of postwar jazz musicians carving out a new identity for black artists, then with a larger movement engaged in transforming the nation’s cultural and political landscape (including the Beats, Civil Rights activists, Abstract Expressionists, and others), it is remarkable that in 1958 he teamed up with arranger Gil Evans to record an album devoted to Porgy and Bess. Ever since its premiere, the opera by the Gershwins and Heyward had sparked controversy and caused Mrican Americans to speak out in protest.